2008
DOI: 10.1007/s10811-008-9390-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the chemical composition of ulvan, a cell wall polysaccharide from Ulva spp. (Ulvales, Chlorophyta) by FT-IR and chemometrics

Abstract: The water-soluble cell wall polysaccharides from green seaweeds of Ulva spp. (Ulvales, Chlorophyta), referred to as ulvan, demonstrate composition-and structure-related functional properties. Mid-infrared spectroscopy combined with chemometric techniques was investigated as a means to rapidly predict the chemical composition of ulvan extracts. A calibration was realized with 41 ulvan extracts from two Ulva species. The variables studied included the constituent sugars (rhamnose, xylose, glucose, galactose, glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
70
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 20 publications
(25 reference statements)
18
70
0
2
Order By: Relevance
“…Matsuo et al [39] isolated, (from an epiphytic marine bacterium), and characterized a causative factor for the induction of normal thallus germination and morphogenesis. Lahaye and Ray [40] found the sugar sequences in the water soluble polysaccharides from Ulvaceae, also Ray and Lahaye [41] as well as Robic et al [42] studied the cell wall polysaccharides of this group using mid-infrared spectroscopy combined with chemometric techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuo et al [39] isolated, (from an epiphytic marine bacterium), and characterized a causative factor for the induction of normal thallus germination and morphogenesis. Lahaye and Ray [40] found the sugar sequences in the water soluble polysaccharides from Ulvaceae, also Ray and Lahaye [41] as well as Robic et al [42] studied the cell wall polysaccharides of this group using mid-infrared spectroscopy combined with chemometric techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention also that ulvan, a major Sulfated Polysaccharide (SP) found in the cell wall of green algae, composed mainly of rhamnose, glucuronic acid, iduronic acid, xylose, glucose, sulphate with small amounts of iduronic acid and traces of galactose and represents 8-29% of the algae dry weight [25,26,[44][45][46][47][48][49][50][51]. The presence of the sulfate groups and the unusual chemical composition and structure of ulvan render it different biological properties [26,52,53].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…In the recent years, ulvan has been extensively investigated for development of novel drugs and functional foods [26,49,53]. Because of its peculiar composition and structure [50], it represents a potential source of new functional biopolymer and it is widely used as biomaterial for tissue engineering in regenerative medicine. Furthermore, studies showed that sulfated polysaccharides can also exhibit beneficial biological activities such as anticoagulant, antiviral, antioxidant, antiinflammatory [54] and antiproliferative [27].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The method was based on the binding of a dye to algal polysaccharides that causes the absorption maximum at 664 nm to decrease linearly over the range of 0-30 μg. In a previous NIRS work, Robic et al (2009) developed a partial least squares (PLS) model to characterise the chemical composition of ulvan, a major polymer of Ulva, with functional properties making it interesting for industrial production. That work focused on determining the chemical composition of the extracted ulvan (Robic et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous NIRS work, Robic et al (2009) developed a partial least squares (PLS) model to characterise the chemical composition of ulvan, a major polymer of Ulva, with functional properties making it interesting for industrial production. That work focused on determining the chemical composition of the extracted ulvan (Robic et al 2009). However, to the best of our knowledge, NIRS has not been used for complete Ulva biomass phenotyping based on its content of major monosaccharides, which are critically important for the rapid selection of macroalgal feedstock for biofuel and biorefinery applications (Golberg et al 2014, Korzen et al 2015a,b, Vitkin et al 2015.…”
Section: Introductionmentioning
confidence: 99%